Engaging Graduate-Level Distance Learners in Research: A Collaborative Investigation of Rural Aging. Issue 1 (2nd January 2016) - O'Connor, Melissa L.; Fuller-Iglesias, Heather; Bishop, Alexander J.; Doll, Gayle; Killian, Timothy; Margrett, Jennifer; Pearson-Scott, Jean
Abstract : Online educational programs pose challenges to nonresidential graduate students for whom research is a key professional development experience. In this article, the authors share their pedagogical approach to engaging graduate-level online distance learners in research. Five students enrolled in an online master's degree program participated in a directed research course designed to facilitate a semester-long, collaborative, hands-on research experience in gerontology. As such, students recruited participants and conducted phone interviews for a multisite study examining aging in place in rural areas. Several strategies were used to facilitate student engagement and learning, including: regular meetings with faculty mentors, creation of a research team across institutions, interactive training, and technological tools to aid in communication. The authors discuss the process of implementing the project, challenges that arose, strategies for dealing with these issues, and a pedagogical framework that could be used to guide future endeavors of this type.